KEKAYAAN PERAIRAN TELUK HOL DAN PANTAI SULAMADAHA YANG BERPOTENSI SEBAGAI DAYA TARIK WISATA DI KOTA TERNATE PROVINSI MALUKU UTARA - SOAMOLE, FITRIA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Sulamadaha beach is an object of interest to tourist that as administration located in Sulamadaha Village, Ternate city of North Moluccas . Sulamadaha beach gives attractions of the tourism nature such as beauty of surface the sea and in the world sea. The mind of this research is to describe the potentials of the object interest tourism In The Hol of Sulamadaha Beach. Descriptive method is used in this research because it to describe the potentials of the object interest tourism. In this research used qualitative method to analyze. The collecting data in this research is recording the informant likes government, tourist and observation. The result of this research applied that waters in Hol of Sulamadaha has the beauty and unique of surface the sea and in the world sea. Surface the likes the nature panorama, the view of the sea, coral, fish and kinds of marine biota that show of the potential of the sea. Keyword: Beauty, unique, water potential, surface of the sea, in the word sea